Economic Inequality Increases the Preference for Status Consumption - Velandia-Morales, Andrea; Rodríguez-Bailón, Rosa; Martínez, Rocío (Frontiers in Psychology, 2022)
Prior research has shown the relationship between objective economic inequality and searching for positional goods. It also investigated the relationship between social class and low income with conspicuous consumption. However, the causal relationship between economic inequality (the difference in wealth between individuals and groups living in a shared context and consumer behavior) has been less explored. Furthermore, there are also few studies looking for the psychological mechanisms that underlie these effects. The current research’s main goal is to analyze the consequences of perceived economic inequality (PEI) on conspicuous and status consumption and the possible psychological mechanisms that could explain its effects. Furthermore, the current research aims to examine whether there is a causal relationship between PEI and materialism preferences and attitudes toward indebtedness. This work includes two preregister experimental studies. In the Study 1 (n = 252), we manipulated PEI and its legitimacy through a 2 (high vs. low inequality) × 2 (Illegitimate vs. legitimate) between-participants experiment. Results showed a main effect of PEI on status consumption, status seeking, status anxiety, materialism, and attitude toward indebtedness. No interaction effect between legitimacy and inequality was found. In the Study 2 (n =301), we manipulated the PEI through the Bimboola Paradigm. We replicated the effect of PEI on status consumption, status seeking, and materialism and found that status seeking mediated the relationship between PEI and status and conspicuous consumption. Economic inequality affects consumer behavior and favors consumption preferences for products that provide desirable symbolic values associated with status. These results could have important implications in the interpersonal and intergroup processes, including those related to consumption and purchase.